তাজউদ্দীন আহমেদের ডায়েরি, ১৯৪৯-১৯৫০, দ্বিতীয় খণ্ড - আহমেদ, তাজউদ্দীন, ১৯২৫-১৯৭৫
Diary of Tājauddina Āhamada, died 1975, prime minister of Bangladesh; autobiographical, translated from English original.